Does ecotourism affect economic welfare? Evidence from Kaziranga National Park, India. Issue 3 (1st September 2016) - Das, Daisy; Hussain, Iftikhar
ABSTRACT: Ecotourism is a market-based conservation strategy which strengthens household economies and improves attitude of people towards conservation efforts. India has tremendous potential for ecotourism. This paper is set in the context of ecotourism activities flourishing around Kaziranga National Park, a World Heritage Site, situated in north east India. The main objectives of the study are to evaluate the perception of respondents towards ecotourism and to examine how participation in this activity affects economic welfare. A field survey is conducted in the periphery villages of the park. We use random sampling to interview households and analyse the data by applying descriptive statistics as well as regression method. The results demonstrate that respondents associated with ecotourism enjoy better living condition, nourish positive attitudes towards this business and feel politically empowered. Ecotourism generates economic welfare by positively and significantly affecting different components of expenditure in the budget of a household. We recommend economic activities based on local resource and skills to generate income in the off-season. Extension of activities related to local culture, festival and other outdoor activities may diversify livelihood. Finally, government has to create an enabling environment along with expansion of eco-development projects, bank loan and training facilities.